Characterization and comparative analysis of ADRs of various ART regimens: experience of our medical college from Western Himalayan region - Sood, Atal; Prajapati, Himani; Bhagra, Suruchi; Bansal, Rekha (International Journal of Research in Medical Sciences, 2017)
Background: It is estimated that there are 35.3 million PLHA worldwide and 1.6 million have received ART. ART is freely available in designated ART Centres. HAART (highly active antiretroviral treatment) has significantly reduced AIDS related morbidity and mortality. It involves using three different drugs from two different classes. The main challenge in prescribing HAART is ADRs associated with it affecting patient compliance and treatment outcomes. Methods: A retrospective observational study was carried out in the ADR monitoring Centre of Dr. Rajendra Prasad Government Medical College, Tanda, Kangra, Himachal Pradesh, India. Results: The data for ADEs was collected from 108 patients over a period of 17 months. A total of 280 ADEs were reported in 65 females and 43 males. TLE was the commonest regimen in 61 (56%) patients followed by ZLN in 37 (34%). Neurological ADRs were reported in 39.8% cases with TLE that was nearly double as reported with ZLN regimen 20.5%. Dermatological ADRs were highest with other regimens (57.4%) followed by ZLN 20.5%. Similarly the frequency of Gastrointestinal ADR was highest with other regimens. Hematological ADRs were maximum with ZLN (22.9%) followed by TLE (3.3%). Most commonly reported ADRs were dizziness (10.7%), rashes (8.2%), anorexia and dyslipidemia (6.8%), asthenia (6.4%), pruritus (6%), joint pains (4.6%), insomnia, alopecia and vomiting (4.3%), numbness or parasthesia (3.9%), hepatotoxicity (3.6%) and deranged RFTs (1.8%). Conclusions: The real burden of ADRs due to ART cannot be estimated until voluntary and mandatory reporting system of ADRs works efficiently. A structured surveillance of the pharmacovigilance system can help to overcome these hurdles to ensure compliance with ART regimens.